STRATEGI GURU DAN SISWA DALAM MENYIKAPI LEARNING LOSS AKIBAT PANDEMI COVID-19 PADA PEMBELAJARAN HYBRID LEARNING DI SMK NEGERI 4 KLATEN - Happy Martama; Lia Samrotul Fuadah; Salsa Septy Mutiarasari; Rayhan Yudhanto (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
It's been almost three years since the Covid-19 pandemic has persisted. Access to the learning process that was previously normal and learning carried out face-to-face has finally changed. In online learning, students feel bored because this learning is less effective. Access to distance learning is still lagging behind, not all students have adequate equipment, and economic limitations make students experience learning loss. There is a qualitative research, namely the descriptive method, the use of this method is because it is more precise in answering the problems that are being researched because it uses direct data from various sources in the field. SMK Negeri 4 Klaten in preparing this Hybrid Learning lesson is in accordance with the policy of the Education Office, the covid-19 task force, apart from that this LMS SMK uses the google classroom service. In addition, it also utilizes thelearning.id account to meet online learning needs. It is hoped that the learning videos that will be sent will make it easier for students to understand theoretical material or practical material, learning videos as a solution for students as well so they don't experience forgetfulness. During the Hybrid Learning learning period there were several solutions that emerged, it was explained that this learning had more social interaction that had increased. Interaction between students, also between teachers and students. From this increase in interaction, during classroom learning and practical learning in the laboratory students are more active in asking questions regarding issues they don't understand. This makes the teachers more enthusiastic in answering and providing problems experienced by students.